The effect of job stress, job satisfaction, and organizational commitment on employee turnover intention at Maya Ubud Resort & Spa - Yudihari, Ni Luh Putu Rita; Puspitawati, Ni Made Dwi; Purnawati, Ni Luh Gede Putu (International Journal of Communication and Society, 2024)
In maintaining potential human resources (HR), there is one obstacle that often occurs and is faced by companies, namely the desire to change jobs (turnover intention) which results in the employee's decision to leave his job. This study aims to examine and obtain empirical evidence of the effect of job stress, job satisfaction, and organizational commitment on turnover intention. The population in this study were all Maya Ubud Resort SPA employees, totaling 264 people. The sample used in this study amounted to 73 employees based on the Slovin formula method. The analysis technique used is the validity test, reliability test, and multiple linear regression analysis. The results showed that job stress has a positive and significant effect on turnover intention, job satisfaction has a negative and significant effect on turnover intention, and organizational commitment has a negative and significant effect on turnover intention.